(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Marina N. Lyasheva (Rostov-on-Don, Russian Federation) The article studies linguacynicisms of informal internet communication. Practical base for the study were social networks that are currently the most relevant, especially among young people. Social networks show shifts and changes taking place in the public consciousness, reflect the mood of the audience. Linguacynicism phenomenon is seen as a product of the cynicism in the evaluation of those who are in the area of moral taboos. Firmly connected to the Internet jargon, linguacynicism is a dangerous phenomenon, i.e. it infringes not only on language but also on the minds of the youth audience, as it is convincingly demonstrated by the presented in the article material. The objects of linguacynicism in online communication become both a specific person, and culturally significant realities, whereas the range of linguacynicism is wide – from a comic effect to sarcasm. Key words: linguacynicism, slang, ecological linguistics, Internet discourse.